Dampak Pembangunan PIK 2 terhadap Pelanggaran Hak Ekonomi Sosial dan Budaya Masyarakat Lokal - Nufus, Saifun (UNIVERSITAS SERAMBI MEKKAH, 2025)
One of the national strategic projects (PSN) is the development of Pantai Indah Kapuk 2 (PIK 2), which is a mega project aimed at creating new growth that significantly impacts various aspects, including the economic, social, and cultural rights of the local community. This research aims to determine the impact of the PIK2 development from the perspective of the economic, social, and cultural rights of the local community, whether this development incorporates aspects of integration and sustainability in accordance with its vision. The method used is a qualitative method with a literature review approach. The research results indicate that the development of PIK 2 can damage coastal ecosystems and pose challenges related to social justice and community participation in planning and decision-making. This study concludes that there is a more just and transparent approach to incorporating environmental sustainability at every stage of the PIK 2 development to achieve progress.